PSIKOEDUKASI REGULASI EMOSI TERHADAP PEMAIN FUTSAL DI SURABAYA LATAR LAYANAN KOMUNITAS FUTSAL DI SURABAYA - Ary Rahmanda Hidayat; Herlan Pratikto (PT. Hasba Edukasi Mandiri, 2025)
Futsal requires not only physical and technical skills but also adequate psychological readiness, particularly in dealing with competitive pressure. One psychological aspect that plays a crucial role in athletic performance is emotion regulation. This study aimed to describe the implementation of emotion regulation psychoeducation for futsal players in the OR community in Surabaya as a form of community-based psychological service. A qualitative descriptive approach was employed using participant observation, semi-structured interviews, and Focus Group Discussions (FGDs) to identify emotional difficulties experienced by the players. The intervention was designed as an emotion regulation psychoeducation program conducted in two offline sessions using a one-group pretest–posttest design. The findings indicated that players experienced difficulties in managing negative emotions such as anger and frustration during high-pressure game situations, which affected individual performance and team dynamics. Following the psychoeducational intervention, players demonstrated improved emotional awareness, more adaptive emotion regulation strategies, and better communication and teamwork. These results suggest that emotion regulation psychoeducation has the potential to be an effective intervention in supporting psychological well-being and performance stability among futsal players in non-formal sports communities.